The Impact of the Covid-19 Pandemic on Infectious Disease Control Regulations in Indonesia - Gusti Bagus Krisna Arum Jati; I Gusti Ngurah Parikesit Widiatedja; Ika Widi Astuti (GLOBAL HEALTH SCIENCE GROUP, 2025)
The COVID-19 pandemic exposed critical fragilities within Indonesia’s legal framework for infectious disease control, manifesting as regulatory fragmentation, overlapping jurisdictional authorities, and asymmetrical human rights protections particularly regarding compensation for vulnerable populations. This study analyses post-pandemic legal transformations, including Law No. 17 of 2023, which incorporates technological innovations yet retains significant gaps in constraining emergency powers and ensuring oversight mechanisms. Comparative analysis with Singapore, Hong Kong, and Thailand reveals divergent approaches to emergency authority delegation, legislative scrutiny, judicial review, and compensatory frameworks. This study utilises 15 primary legal sources. Additionally, 19 secondary legal materials, published between 2019 and the issuance of Presidential Decree of the Republic of Indonesia Number 17 of 2023 concerning the Declaration of the End of the Coronavirus Disease 2019 (COVID-19) Pandemic Status, are employed. Furthermore, five tertiary legal materials are used. These legal materials serve as the basis for examining the identified legal issues. The legal material analysis technique adopted in this study involves descriptive analysis, which includes expert opinions, conclusions, legal interpretations, and comparative legal analysis. The resurgence of COVID-19 in neighbouring states underscores the imperative for sustained preparedness. We recommend: (i) comprehensive statutory revisions; (ii) regulatory harmonisation; (iii) establishment of independent dispute-resolution mechanisms; (iv) enactment of robust health data protection legislation; and (v) enhanced surveillance and risk communication capacities. These reforms are fundamental to constructing a legally resilient, adaptive, and equitable system capable of mitigating future pandemic threats while balancing public health imperatives with constitutional safeguards.